Effect of mobilization time by maitland method in nonspecific low back pain and neck pain. - Aguiar, Luís Eugênio Silva de; Oliveira, Mafra Raiele Torres; Caldas, Rafael Rêgo; Correia, Mariana Cavalcanti; Rocha, Sérgio; Carneiro, Maíra Izzadora Souza; Tenório, Angélica da Silva; Guerino, Marcelo Renato; Monte-Silva, Kátia Karina; Araújo, Maria das Graças Rodrigues de (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Maitland method is a technique of manipulation and joint mobilization to reduce pain, recovery of mobility and joint alignment. Objective: to analyze the effects of spinal manipulation in Maitland pains of cervical and lumbar spine, considering reducing the exposure time of each maneuver on pain, range of motion and muscle function. Method: Eleven randomly patients assigned to two groups: (i) Experimental Conventional (GEC;06): conventional technical indications, (ii) Experimental Modified (GEM;05): protocol with the same maneuvers, but reduced application time. All evaluated before (t0) and after (t1) the period of therapeutic sessions with Visual Analogue Scale (VAS) for pain, Flexibility Test Bank with Wells and Surface Electromyography (EMG) for muscle electrical activity of the cervical and lumbar regions. The data were statistically analyzed; p <0.05. Results: In GEM pain decreased significantly (p=0.047), muscle electrical activity in the cervical region showed a significant trend (p=0.068). Flexibility in GEC was improved, but not significantly. tended Root Mean Square in the cervical region of the GEM (p=0.068) to achieve significant value, but this trend was not observed in GEC. In the lumbar region there were no differences in both groups. Conclusion: Volunteers in both groups had positive results even though not statistically significant. The effects of reduced time and time recommended by Maitland (1 minute) the sessions were effective in decreasing symptoms, pain and restricted joint mobility, but we consider important to continue further studies in this knowledge and practice of physical therapy area.